Aerobic Degradation of 2,4,6-Trinitrotoluene by Enterobacter cloacae PB2 and by Pentaerythritol Tetranitrate Reductase - French, Christopher E. (American Society for Microbiology, 1998)
Enterobacter cloacae PB2 was originally isolated on the basis of its ability to utilize nitrate esters, such as pentaerythritol tetranitrate (PETN) and glycerol trinitrate, as the sole nitrogen source for growth. The enzyme responsible is an NADPH-dependent reductase designated PETN reductase. E. cloacae PB2 was found to be capable of slow aerobic growth with 2,4,6-trinitrotoluene (TNT) as the sole nitrogen source. Dinitrotoluenes were not produced and could not be used as nitrogen sources. Purified PETN reductase was found to reduce TNT to its hydride-Meisenheimer complex, which was further reduced to the dihydride-Meisenheimer complex. Purified PETN reductase and recombinant Escherichia coli expressing PETN reductase were able to liberate nitrogen as nitrite from TNT. The ability to remove nitrogen from TNT suggests that PB2 or recombinant organisms expressing PETN reductase may be useful for bioremediation of TNT-contaminated soil and water.